THE ROLE OF DIPLOMACY IN PEACE STUDY: A CASE STUDY OF SAUDI ARABIA AND IRAN - Muhammad Siddique (International Journal of Contemporary Issues in Social Sciences, 2023)
The complex relationship between Saudi Arabia and Iran, two major participants in regional equilibrium and global political currents, has a significant impact on the region’s geopolitical dynamics. The complex history, contemporary developments, and uncertain future of Saudi-Iranian relations are all explored in this book. With Saudi Arabia’s Sunni hegemony and Iran’s Shia domination influencing their ongoing conflict, this article takes a critical look at the diplomatic engagements that reflect the underlying religious split. From the holy sites of Mecca and Medina, Saudi Arabia exerts unmatched religious authority over the rest of the Sunni Muslim world. According to Esposito (2002), this special kind of soft power results from the intersection of religious authority and historical significance. Iran, on the other hand, has carved itself a considerable cultural and geopolitical niche, sometimes at odds with Saudi objectives, thanks to its rich Persian past and the adoption of Shia Islam by the Safavid dynasty in the 16th century. The wider effects of the Saudi-Iranian struggle for preeminence are evaluated, including strategic measures formed in response to complicated regional tensions, global sanctions, and unpredictable oil markets, and conflicts in the Persian Gulf and current fighting in Yemen and Syria offer context for the two superpowers’ continuous rivalry and eventual reconciliation. The paper also considers how recent diplomatic efforts and the realignment of international alliances have altered the bilateral relationship paradigm. By giving a complete narrative of the historical backdrop and contemporary events, this inquiry gives a comprehensive view on how Saudi Arabia and Iran negotiate their fabled and controversial relationship, despite evolving geopolitical landscapes.